Has Growth in Supply of Educated Persons Been Important for the Composition of Employment? - Nils Martin Stølen; Turid Åvitsland (Statistics Norway, Research Department, 1997)
In the Norwegian fabricated metal industry there has been a shift in demand from unskilled to skilled workers during the period 1972 to 1990, and relative demand for white collar employees has also increased. The paper analyses the factors behind the shift in the composition of these three kinds of labour. A translog cost function approach is applied, using an error-correction representation of the development in cost shares. The results indicate substitutability between unskilled and both skilled and white collar workers. Increased supplies of skilled workers and engineers seem to have been the most important factors for the change in the composition of employment, indicating lack of persons with these kinds of education. In addition, unskilled workers have been rationalized away as a result of technical progress.
Keywords: J21; J23; J31; 330; Labour market; employment composition; human capital; wage differentials; time series analysis.